SOCIAL COHESION AND CONFLICT AS SHAPERS OF SOLIDARITY AND COLLECTIVE IDENTITY OF PERSIS SOLO SUPPORTERS ORGANIZATION/COMMUNITY - Ridlo Febi Wicaksono (The Indonesian Journal of Social Studies, 2025)
This research aims to understand the supporter group, the forms of solidarity, and the efforts in conflict mediation within the PERSIS Solo supporter group. This study uses Ferdinand Tonnies' organizational theory, Emile Durkheim's social solidarity theory, and Ralf Dahrendorf's conflict theory. The method in this research is qualitative interpretative. The primary data sources come from figures within the supporter groups, and the secondary data sources come from literature studies. The results of this research show that the solidarity formed between the two PERSIS Solo supporter groups includes (1) Away, (2) Criticism of the club, (3) Celebrating PERSIS's victory, (4) Podo-podo supporting PERSIS , ngopo ndadak gelutan , (5) Bhinneka Tunggal PERSIS, and (6) I'm happy with PERSIS, Kowe happy with PERSIS, krudewe sedulur . Meanwhile, the conflicts that arise between the two PERSIS Solo supporter groups are (1) conflicts inside the stadium, such as the conflict between Pasoepati in the B7 stand and Surakartans 1923 in the B6 stand, and (2) conflicts outside the stadium, such as confrontations outside. As for the mediation efforts within the PERSIS Solo supporter groups, they include (1) bringing the conflicting parties together, (2) assistance from the police, (3) maintaining the conducive atmosphere of Solo City, and (4) Legowo.